The Evolving Value of Foreign Partnerships in Transitioning Economies - Steensma, H. Kevin; Tihanyi, Laszlo; Lyles, Marjorie A.; Dhanaraj, Charles (Academy of Management Journal, 2005)
Through studying joint ventures during the early (1993) and late phases (2001) of Hungary's economic transition to market economy, we demonstrate how institutional and economic transformation alters foreign parents' roles in the success of joint ventures. Foreign parent decision influence and resource provision affected market performance and knowledge acquisition differently in the two phases. We conjecture that the value of foreign partner involvement in a transition economy depends in part on the maturity of the transition.